2020
DOI: 10.1111/dmcn.14654
|View full text |Cite
|
Sign up to set email alerts
|

24‐hour activity for children with cerebral palsy: a clinical practice guide

Abstract: The association between physical activity and health has been clearly established, and the promotion of physical activity should be viewed as a cost‐effective approach that is universally prescribed as a first‐line treatment for nearly every chronic disease. Health care providers involved in the care for individuals with cerebral palsy (CP) are encouraged to take an active role in promoting their health and well‐being. Balancing activity behaviours across the whole day, with improved physical activity, reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“… 15 Second, the checklist is not a validated screening instrument but was designed as a practical tool to open and facilitate the conversation about sleep with parents in the health care setting. 18 In contrast to more extensive sleep screening tools like the Sleep Disturbance Scale for Children, the 24‐hour activity checklist includes questions about parental sleep. This not only gives an insight into the impact of sleep problems beyond the child, it also stimulates a family‐centred care for sleep, an important wish of parents of children with CP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 15 Second, the checklist is not a validated screening instrument but was designed as a practical tool to open and facilitate the conversation about sleep with parents in the health care setting. 18 In contrast to more extensive sleep screening tools like the Sleep Disturbance Scale for Children, the 24‐hour activity checklist includes questions about parental sleep. This not only gives an insight into the impact of sleep problems beyond the child, it also stimulates a family‐centred care for sleep, an important wish of parents of children with CP.…”
Section: Discussionmentioning
confidence: 99%
“…Parents completed the 24‐hour activity checklist, a brief questionnaire developed to assess the physical activity and sleep patterns of the child and parental sleep. 18 For the purpose of the present study, responses to the Sleep section of the 24‐hour activity checklist (Fig. S1 , online supporting information) were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Going forward, it is suggested that a simpler first screen using questionnaire-based measures should precede the COS. For example, members of our team recently published on the pilot testing of a 24-hour activity checklist for children with CP. 16 The checklist includes questions about physical activity, screen time, and sleep that can be completed by the patient and family before their clinical appointment. We suggest clinicians should include a shortform physical activity questionnaire alongside the PSQI and SFFFQ questionnaires as a first screen and then proceed to the remainder of the COS or certain aspects of the COS that might be most relevant to the patient (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Improving sleep can alone prove a worthwhile goal of adaptive sports in children with PIMD, given the high frequency of sleep disorders in this population and the spiralling negative effects of sleep deprivation on the children’s and families’ health and wellbeing [ 33 ]. Recent guidelines have emphasised the importance of taking into account both physical activity and sleep around-the-clock to improve the health and quality of life outcomes of children with neurological disabilities [ 34 ].…”
Section: Discussionmentioning
confidence: 99%